Brachyspira hyodysenteriae Infection Reduces Digestive Function but Not Intestinal Integrity in Growing Pigs While Disease Onset Can Be Mitigated by Reducing Insoluble Fiber - Helm, Emma T.; Lin, Susanne J.; Gabler, Nicholas K.; Burrough, Eric R. (Frontiers in Veterinary Science, 2020)
Swine dysentery (SD) induced by Brachyspira hyodysenteriae manifests as mucohemorrhagic diarrhea in pigs, but little is known about the changes that occur to the gastrointestinal tract during this disease. It is thought that dietary fibers alter disease pathogenesis, although the mechanisms of action are unclear. Thus, the objectives of this study were to characterize intestinal integrity, metabolism, and function in pigs during SD and determine if replacing insoluble fiber with fermentable fibers mitigates disease. Thirty-six B. hyodysenteriae negative gilts (24.3 ± 3.6 kg BW) were assigned to one of three treatment groups: 1) B. hyodysenteriae negative, control diet (NC), 2) B. hyodysenteriae challenged, control diet (PC), and 3) B. hyodysenteriae challenged, highly fermentable fiber diet (RS). The NC and PC pigs were fed the same control diet, containing 20% corn distillers dried grains with solubles (DDGS). The RS pigs were fed a diet formulated with 5% sugar beet pulp and 5% resistant potato starch. On days post inoculation (dpi) 0 and 1, pigs were inoculated with B. hyodysenteriae or sham. Pigs were euthanized for sample collection after onset of SD. The challenge had high morbidity, with 100% of PC and 75% of RS pigs developing clinical SD. The timing of onset of clinical SD differed due to treatment, with RS pigs having a delayed onset (dpi 9) of clinical SD compared with dpi 7 for PC pigs. Colon transepithelial resistance was increased and macromolecule permeability reduced in PC pigs compared with NC pigs (P<0.01). Minimal changes in ileal permeability, mitochondrial function, or VFAs were observed. Total VFAs concentrations were lower in the colon and cecum in both PC and RS pigs compared to NC pigs (both P< 0.05), but iso- acids were higher (both P< 0.05). Total tract digestibility of DM, OM, N, and GE was lower in PC pigs compared with both NC and RS pigs (both P< 0.001). These data indicate that SD reduces digestive function but does not reduce ex vivo intestinal integrity. Further, replacement of insoluble fiber with highly fermentable fibers mitigated and delayed onset of SD.